The 21st century surgeon between tradition and modernity: Dr. Phillipe Marre - Marre, Phillipe; Ruso Martinez, Luis (Cirugía del Uruguay, 2025)
Free translation by Dr. Luis Ruso Martínez, with permission of the author Dr. Phillipe Marre, of the closing conference of the “Recontres Internacionales de la Chirurgie Francophone” (RIFC 2024), given in Paris on October 27, 2024. “Le chirurgien du siècle XXI entre la tradition et la modernite.” Dr. Marre is professor (R) of visceral and digestive surgery and one of the precursors of bariatric surgery in France. He is a full member and President (2021) of the French National Academy of Surgery.